2019
DOI: 10.3389/fimmu.2019.00195
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Highly Variable, Region-Specific Patterns of T-Cell Epitope Mutations Accumulating in Mycobacterium tuberculosis Strains

Abstract: Vaccines that confer protection through induction of adaptive T-cell immunity rely on understanding T-cell epitope (TCE) evolution induced by immune escape. This is poorly understood in tuberculosis (TB), an ancient, chronic disease, where CD4 T-cell immunity is of recognized importance. We probed 905 functionally validated, curated human CD4 T cell epitopes in 79 Mycobacterium tuberculosis (Mtb) whole genomes from India. This screen resulted in identifying 64 mutated epitopes in these s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 66 publications
(117 reference statements)
0
5
0
Order By: Relevance
“…We analyzed the sequence of phoR in 242 mycobacterial strains from BioProject PRJNA235851 in National Center for Biotechnology Information (NCBI) ( Ramaiah et al, 2019 ) with a combination of drug-sensitive/resistant, polydrug- and multidrug-resistant cohort of a South Indian population ( Ramaiah et al, 2019 ) with H37Rv as the reference sequence to identify various SNPs, and we found one that translated into a non-synonymous, missense mutation in the protein. This SNP changed alanine to threonine residue (A400T) at the 400th position, in the HATPase domain ( Figures 1A,B ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We analyzed the sequence of phoR in 242 mycobacterial strains from BioProject PRJNA235851 in National Center for Biotechnology Information (NCBI) ( Ramaiah et al, 2019 ) with a combination of drug-sensitive/resistant, polydrug- and multidrug-resistant cohort of a South Indian population ( Ramaiah et al, 2019 ) with H37Rv as the reference sequence to identify various SNPs, and we found one that translated into a non-synonymous, missense mutation in the protein. This SNP changed alanine to threonine residue (A400T) at the 400th position, in the HATPase domain ( Figures 1A,B ).…”
Section: Resultsmentioning
confidence: 99%
“…The sequences of 19 clinical isolates from India, reported as part of a previous study ( Ramaiah et al, 2019 ), along with 223 sequences from BioProject PRJNA235851 ( Manson et al, 2017 ), were analyzed and aligned using T-COFFEE and CLUSTALW ( Madeira et al, 2019 ) using the phoR gene sequence from H37Rv strain as a template. A variation from g cc to a cc at the 1,198 nucleotide of phoR gene was identified and named PhoR’ (A400T).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, amino acid variants in 10 out of 14 experimentally tested epitopes led to differential immune responses, as measured by IFN-y secretion in the blood of 82 individuals from the Gambia, latently infected with M. tuberculosis [ 61 ]. Other elaborated approaches have been also uncovering relevant CD4 + T cell epitopes, including some that are highly prevalent in certain MTBC lineages [ 62 , 63 , 64 ]. Another important feature of the immune response in TB is the balance between pathogen clearance and immunopathology [ 8 , 10 ].…”
Section: Genetic Diversity Of M Tuberculosismentioning
confidence: 99%
“…Over the course of the infection, immunity develops, targeting of specific antigens arises, the infection is suppressed, and re-infection by the same pathogen later hindered. On the other hand, immune responses to mycobacterial pathogens like M. tuberculosis are well-known to be more nuanced and skewed towards a cell-mediated immune response 4,8,9 . Early research suggested a limited role of B cells or antibodies in protection, and although these subsets do have beneficial roles 3,10,11 , it is known that a successful immune response against MTB infection absolutely requires CD4 + and CD8 + T cell activity 2,3,12 .…”
Section: Introductionmentioning
confidence: 99%